Study on Anaplasma, Borrelia, Coxiella, Ehrlichia, Rickettsia and Hepatozoon agents in ticks (Acari: Ixodoidea: Argasidae, Ixodidae) from Chile, and a taxonomic study on Ornithodoros capensis sensu lato (Acari: Argasidae) in South America São Paulo - Leal, Sebastián Alejandro Muñoz (2017)
Until 2014, scientific knowledge on the diversity of Chilean Ixodoidea summarized 19 species and only agents of Borrelia and Rickettsia genera had been detected. The objectives of this study were to evaluate the occurrence of further agents of Anaplasma, Borrelia, Coxiella, Ehrlichia, Rickettsia and Hepatozoon by means of molecular tools. Obtained sequences were inserted into a phylogenetic context in order to evaluate their relatedness to microorganisms of know pathogenic roles. As agents of Coxiella genus resulted to be related to endosymbiotic bacteria, data on these organisms was used to perform a taxonomic study with ticks of the Ornithodoors capensis sensu lato complex. The results confirm that Chilean ticks harbor at least three new borrelial, one new rickettsial, and three new Hepatozoon species for science. Moreover, Rickettsia amblyommatis, Rickettsia hoogstraalii and Rickettsia lusitaniae are added to the list of Chilean rickettsiae. Although ticks were positive to Anaplasmataceae PCRs, an accurate study including longer fragments of the 16S RNA targeted gene must be performed in order to confirm their specific identity. Coxiella-like endosymbionts are specific of every of the four O. capensis s. l. species analyzed in this study, and therefore constitute a useful tool in order to confirm the identities and define genetic boundaries of ticks of this group in South America. Finally, the results of this study add at least five new species of Argasidae family into Chilean fauna of ticks, and point the occurrence of several forms that need further assessment in order to accurately confirm their identities.